Avaliação de aptidão física em atletas profissionais - Zamberlan, Elói; Kamide, Roberto (Semina: Ciências Exatas e Tecnológicas, 2004)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0pt; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 85.05pt 70.85pt 85.05pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> This paper discusses the result of the physical fitness evaluation carried out with professional soccer athletes in Pa-rand State teams. The author obtained the results from general kinds of physical measurements such as: oxygen consumption, adductor muscle elasticity, muscular strength of the superior and inferior members, basic speed (50 m) and abdominal muscle resistance. The author analyzed 119 professional athletes (7 teams) from Parana State soccer championship (special league). He divided the players into four groups according to their position during the game Group I - Outsides and insides Group II - Forwards Group III - Fullbacks and centre-forwards Group IV - Centerhalf The author expects that these results will help the coaches examine the efficiency of the methodology applied to the professional athletes training in terms of the obtained practical results